Pendampingan Teknis Penanaman Tanaman Pepaya California sebagai Upaya Meningkatkan Motivasi Masyarakat dalam Pengusahaannya - Ariyanti, Mira; Erni Suminar; Santi Rosniawaty (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Fruits with various benefits include papaya. The price of papaya fruit is relatively affordable, making it possible to make it a fruit that is popular with all levels of Indonesian society. One type of papaya is California papaya which has several advantages compared to other types, namely the taste is sweeter, the fruit is not too large, the fruit skin is shiny with thick and chewy flesh. This makes it important to introduce California papaya to the people of Cinanjung Village, Tanjungsari District, Sumedang Regency. Apart from the climatic conditions in the Cinanjung Village area which is suitable for planting papaya plants, it is also supported by the social conditions of the community where most of them work in the agricultural sector.This activity aims to encourage people to plant California papaya using good cultivation methods so that the results can be enjoyed by the people in the village. This activity is expected to motivate the people of Cinanjung Village to like local fruit and seriously cultivate it, which in the end can be used as a source of income. The methods used include location surveys, counseling (presentation of material, filling out questionnaires on participants' level of knowledge), distribution of California papaya seeds, and assistance with papaya cultivation techniques. The result of this activity is that the community obtains additional information regarding how to carry out California papaya cultivation techniques and apply these techniques to their cultivation activities.